The Role of English Training Camp in Improving Students’ Speaking Skill - Rahmadiani, Sukma; Mahyuni; Thohir , Lalu (LITPAM, 2026)
This study aims to identify specific activities within the English Training Camp that contribute to improving students' speaking skills and to explore students' perceptions regarding the effectiveness of these activities at the Nurul Haramain Islamic Boarding School. A descriptive qualitative research design was employed. The participants consisted of three tutors and 15 students actively participating in the English Training Camp program, selected from a total population of 200 students. Data were collected through observation, interviews, and questionnaires, and subsequently analyzed using the stages of data reduction, data display, and conclusion drawing. The results indicate that the English Training Camp positively contributes to enhancing students' speaking skills through the various activities organized, with